Channel morphometrics calculated for the mainstem Rio Bermejo - Repasch, Marisa N; Scheingross, Joel S; Cook, Kristen L; Sachse, Dirk; Dosch, Sophia; Orfeo, Oscar (In: Repasch, MN et al. (2023): River water chemistry, channel morphometrics, and river incision data for the Rio Bermejo, Argentina [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.959938, 2023)
River distance, elevation, and slope were calculated in ArcMap using the TanDEM-X DEM (for elevation and slope) and using the 2015 Landsat 7 imagery (for river distance). River width and channel belt width were calculated using the ChanGeom algorithm (Fisher et al., 2013; doi:10.1016/j.geomorph.2013.04.011).
Keywords: Argentina; channel migration rates; fluvial geomorphology; Foreland basin; river morphometrics; water chemistry